KAJIAN BUDAYA VISUAL DALAM ILMU KOMUNIKASI: POSISI DAN METODE PENELITIAN - Adde Oriza Rio (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2011)
AbstractThe centrality of the eye and visual ability in the life of individuals and society has spawneda form of culture that is called as visual culture. Visual culture studies are a burgeoningarea of study that emphasizes the complex interrelationship between visual image, cultureand spectators of visual image. On the other hand, communication practices that utilizevisual messages as means of interaction are also increasingly prevalent as this is driven bythe development of visual and communication technology which allows peoples to producetheir own visual image as messages to communicate them. This article tries to discuss theposition of visual culture studies within the communication science and the researchmethods that can be used in the communication science to examine visual image, culture,and spectatorships.Keywords: Visual culture, Visual culture studies, Visual communication,Communication science, Visual methodologies.